Evaluation of antioxidant properties, cytotoxicity and acute oral toxicity of Gynura procumbens (Compositae) - Wuen, Yew Teoh; Norhanom Abdul Wahab,; Richardson, Jaime Stella Mose; Kae, Shin Sim (Universiti Kebangsaan Malaysia, 2016)
Gynura procumbens which is locally known as ‘Sambung nyawa’ in Malay and ‘Feng Wei Jian’ in Chinese, belongs to the botanical family of Compositae. In this study, antioxidant property of G. procumbens extracts was evaluated using DPPH radical scavenging, metal chelating and β-carotene bleaching assays. To the best of our knowledge, this is the first report that evaluated the cytotoxicity of G. procumbens extracts on human colon cancer cells (HT-29, HCT 116, HCT-15, SW480, Caco-2) and human normal colon cells (CCD-18Co). The results showed that ethyl acetate extract contained the highest total phenolic content (172.68 mg of GAEs/g of extract) compared to methanol, hexane and water extracts. Methanol extract possessed better overall antioxidant activities while ethyl acetate extract demonstrated better cytotoxic activity. At 24 h treatment, ethyl acetate extract demonstrated selective cytotoxicity against HT-29 and HCT 116 cells with IC50 values of 35.7 and 42.6 µg/mL, respectively. In addition, methanol extract showed negligible level of toxicity when administered orally. All the results indicated that G. procumbens may provide benefits in prevention and treatment of cancer.